Morpho-anatomical characteristics conferring drought tolerance in roots of sugar cane genotypes (Saccharum L., Poaceae) - da Cruz Maciel, Jean Rafael; de Oliveira, Danielle; Fadin, Dauri Aparecido; das Graças Sajo, Maria [UNESP]; Pedroso-de-Moraes, Cristiano (Springer Nature, 2015)
Sugar cane is a major product of Brazilian agriculture, providing about R$ 56 billion of exports per year. Morphological and anatomical analyses enable the identification of plants, whose genotype is still unknown, and increase our knowledge of organs adaptations, such as roots, to different environment conditions. This study aimed to describe the morpho-anatomy of roots of six sugar cane genotypes. Plants were obtained by insertion of stalks in 3L containers filled with coconut fiber substrate. They were held for 7 days in a germination chamber (BOD MA 403) under a 16-h photoperiod with a light intensity of 38 μmol m−2 s−1 and a constant temperature of 35 °C. Daily irrigation was performed, keeping the substrate close to saturation. After this period, plants were transferred to a greenhouse and grew under approximately 116 μmol m−2 s−1 of light intensity at 30 °C and 80 % relative humidity, during 45 days of daily irrigation. For anatomical characterization, 20 roots from stalks and tillers of five plants per genotype were fixed in FAA 50 % and preserved in alcohol 70 %. For each root, the median region was selected for freehand-sectioning, using a razor blade. The results confirmed that anatomical features might be useful for cultivar identification. RB867515 cultivar showed roots with anatomical features that provide drought resistance, including a reduced number of cortical layers. The roots of SP801816 cultivar had more cortical layers and protoxylem poles in stalks and tillers, indicating a reduced drought resistance.
Keywords: Cortex; Exodermis; Protoxylem poles; Root anatomy